Increased serum soluble PD-l1 levels in patients with advanced stages of chronic kidney disease - Hayashi, Ayaka; Ishihara, Hiroto; Kawabe, Mayuko; Kato, Kazuhiko; Nakashima, Akio; Yamamoto, Izumi; Sakano, Teppei; Kobashi, Hiroe; Morita, Makoto; Yokoo, Takashi; Urashima, Mitsuyoshi (Frontiers in Medicine, 2025)
BackgroundProgramed death-ligand 1 (PD-L1) is overexpressed on renal tubular and vascular epithelial cells in inflammatory kidney diseases as well as on aged kidney podocytes, contributing to chronic kidney disease (CKD) progression. The association of serum soluble programed death-ligand 1 (sPD-L1) levels and chronic kidney disease (CKD) progression is unknown.MethodsTo compare serum sPD-L1 levels among healthy individuals and patients with various CKD stages, including those undergoing dialysis, a secondary analysis was performed using clinical data and residual serum samples from four distinct cohorts, each prospectively collected for different research purposes: The Vaccine Cohort (2021–2022), the Cancer Cohort (2010–2018), the Dialysis Initiation Cohort (2023–2024), and the Dialysis Maintenance Cohort (2011–2015) included patients on stable maintenance dialysis.ResultsThe study analyzed serum sPD-L1 levels in 2,829 participants (mean age, 54.2 years; male, 54.2%) across the four cohorts. In the Vaccine and Cancer cohorts, sPD-L1 levels increased significantly with age (P < 0.001) and male sex (P < 0.001). In the Vaccine Cohort, elevated median sPD-L1 levels (pg/mL) were significantly associated with CKD stage progression (P < 0.001), showing exponentially higher levels with CKD progression. A similar association was observed and validated in the Cancer Cohort (P < 0.001). In the Dialysis Initiation Cohort (n = 15), sPD-L1 levels significantly increased three months after dialysis initiation compared to pre-dialysis levels (P = 0.03). In the Dialysis Maintenance Cohort, sPD-L1 levels increased with longer dialysis duration (P < 0.001).ConclusionSerum sPD-L1 levels might increase with CKD stage progression, dialysis initiation and longer dialysis duration. Further clinical investigation is required to confirm these results.